1997
DOI: 10.1073/pnas.94.19.10069
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for protein X binding to a discontinuous epitope on the cellular prion protein during scrapie prion propagation

Abstract: Studies on the transmission of human (Hu) prions to transgenic (Tg) mice suggested that another molecule provisionally designated protein X participates in the formation of nascent scrapie isoform of prion protein (PrP Sc ). We report the identification of the site at which protein X binds to the cellular isoform of PrP (PrP C ) using scrapieinfected mouse (Mo) neuroblastoma cells transfected with chimeric Hu͞MoPrP genes even though protein X has not yet been isolated. Substitution of a Hu residue at position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
426
1
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(447 citation statements)
references
References 44 publications
15
426
1
5
Order By: Relevance
“…Intriguingly, residues Q167, Q171, V214, and Q218 have been identified as the binding site for the socalled ''protein X''. 56 These residues exhibit, or are sequentially adjacent to residues that exhibit, R ex motions. The binding of an as yet, unidentified molecule might destabilize PrP C or stabilize a PrP* intermediate.…”
Section: Prp C Folding Intermediates and Stabilitymentioning
confidence: 99%
“…Intriguingly, residues Q167, Q171, V214, and Q218 have been identified as the binding site for the socalled ''protein X''. 56 These residues exhibit, or are sequentially adjacent to residues that exhibit, R ex motions. The binding of an as yet, unidentified molecule might destabilize PrP C or stabilize a PrP* intermediate.…”
Section: Prp C Folding Intermediates and Stabilitymentioning
confidence: 99%
“…However, insights into the normal function of PrP C , and the extent to which conformational alterations might participate in this function, have proven hard to come by because of difficulties in connecting in vitro and in vivo data. For example, in vitro protein binding partners have proven difficult to authenticate by in vivo genetic analyses, and conversely, in vivo genetic analyses of PrP C have been limited to defining determinants required for prion replication and binding to an as yet uncloned partner protein designated protein X (2,3). Other recent areas of interest and controversy concern the basis of neurotoxicity and the existence and function of cytoplasmic forms of PrP C (4 -9).…”
mentioning
confidence: 99%
“…Investigations have also revealed that the S2-H2 loop plays a principal role in the pattern-driven propagation of a prion (Kaneko et al 1997), acts as a motif with selfaggregation properties and is a universal interference target for familial prion diseases, but mutations cause the loss of the binding sites for inhibitors and the gain of an interacting region at the amyloid-forming S2-H2 loop (Meli et al 2011). Alteration of conformation of the S2-H2 loop region leads to the exposure of hydrophobic cluster to solvent, which facilitates intermolecular interactions involved in spontaneous generation of PrPSc (Biljan et al 2011).…”
Section: Resultsmentioning
confidence: 99%